Trust and Awareness of Online Pharmacies in India - Stephen Rajasekharan (International Journal of Advanced Science and Technology, 2020)
With advent of technology, there has been a technological advancement in selling of medicines. Sale of medicine has found a new channel of sales which is the e-commerce space. This channel has been called as the online pharmacy. Online pharmacy has come into existence very recently in the Indian markets, yet have grown and made its presence in the pharmaceutical space. The reason for its growth is the kind of a business model these online pharmacies have. Which is more customer-centric and more advantageous to the customers. However online pharmacy has been able to acquire only 1% of the market share and remaining 99% is still being catered by retail pharmacies. Trust and awareness are one of the important factors in consumer purchase journey. Its one of deciding factors in the purchase of medicines online. In this research paper a primary research was done to understand the reasons or the level of trust and awareness people have in online pharmacies. In this research paper, we have described online pharmacies, the business model, products available, its customer base, advantages & disadvantages, present scenario, trust and awareness. This research paper will give us an understanding the level of trust and awareness people have on online pharmacies. The key findings of the study were majority of the respondents knew about online pharmacies, had some basic knowledge about it, close to 38% of the respondents have already purchased medicines from online pharmacies in the past, most of the respondents believe that online pharmacies share detailed information about the products sold and they also believe that online pharmacies do not sell fake or spurious medicines, and lastly more than half the respondents are likely to purchase medicines from online pharmacies in the future.